2018
DOI: 10.1016/j.jaci.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy: A review and update on epidemiology, pathogenesis, diagnosis, prevention, and management

Abstract: This review provides general information to serve as a primer for those embarking on understanding food allergy and also details advances and updates in epidemiology, pathogenesis, diagnosis, and treatment that have occurred over the 4 years since our last comprehensive review. Although firm prevalence data are lacking, there is a strong impression that food allergy has increased, and rates as high as approximately 10% have been documented. Genetic, epigenetic, and environmental risk factors are being elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
977
2
79

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,230 publications
(1,165 citation statements)
references
References 233 publications
16
977
2
79
Order By: Relevance
“…Alergija predstavlja čest i kontinuirano rastući oblik nepodnošenja hrane u dečjoj dobi [1][2][3][4][5]. Znatno je učestalija u razvijenim u odnosu na zemlje u razvoju [6,7].…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Alergija predstavlja čest i kontinuirano rastući oblik nepodnošenja hrane u dečjoj dobi [1][2][3][4][5]. Znatno je učestalija u razvijenim u odnosu na zemlje u razvoju [6,7].…”
Section: Uvodunclassified
“…Znatno je učestalija u razvijenim u odnosu na zemlje u razvoju [6,7]. Generalno gledano, sreće se kod 2-8% dece i to uglavnom u dobi odojčeta i malog deteta [4][5][6][8][9][10]. Poremećaj je najčešće prolaznog karaktera i primarno pogađa nasledno predisponiranu decu, a posebno odojčad u prvom polugođu po rođenju i na veštačkoj ishrani ili dohrani [6,[11][12][13].…”
Section: Uvodunclassified
“…Especially children are in danger of anaphylaxis to low amounts of allergen. They contribute significantly to the frequent attendance at the emergency rooms due to unintentional ingestion of foods contaminated by hidden allergens [4-6]. The pathomechanisms that contribute to the development and maintenance of PA involve antigen-presenting cells, mast cells, T cells, and B cells [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Peanut allergy is one of the most common food allergies, with a prevalence of approximately 1% in the general population, and recent studies have suggested that its prevalence is on the rise [1]. Peanut allergy is more persistent than other food allergies, and resolution is only seen in 20% of cases, unlike many other food allergies that are usually outgrown by the age of 16 years [25].…”
Section: Introductionmentioning
confidence: 99%